A comparative study of acoustic- and centrifugation-based cell wash - Linander,Oskar (2019)
Cell handling is an important aspect of biomedical research, as an accurate cell media composition and cell viability is paramount for successful studies. Specifically cell washing, the replacement of the liquid media in which the cells are dispersed with another liquid media, has been studied in this thesis. An acoustofluidic device called the AcouWash, by AcouSort AB, which utilizes the combination of acoustophoretic forces generated by sound with the predictable laminar flows of microfluidics, was evaluated compared with a manual three-step centrifugation cell wash. By washing 5 µm polystyrene beads in PBS (Phosphate Buffered Saline) with fluorescein and neuroblastoma cancer cells in PBS with FBS (Fetal Bovine Serum), the recovery of beads/cells and fluorescein/FBS washing efficiency of respective cell washing method was measured. The results showed that the AcouWash in terms of recovery performed at an equal level as manual centrifugation wash, with very close to 100% recovery of beads. However, in washing efficiency, it was only able to perform equal to a two-step centrifugation wash and was not quite on the same level as the three-step centrifugation wash. In terms of reproducibility, no statistically significant difference between an individual operator and multiple operators performing the manual centrifugation washes was found. Although, it is believed that this could change with a larger variety of operators and more repeats. A viability study using neutrophils was performed, where it was investigated whether the AcouWash or manual centrifugation wash could cause unintentional neutrophil activation (NET formation) or cell death. No cell death due to any of the cell washing methods was found. Depending on how the results from the neutrophil experiment is interpreted, either the AcouWash and centrifugation did not have any significant effect on neutrophil activation or, if the pooled samples results are to be believed, the AcouWash may also remove activated neutrophils (NETs) from non-activated neutrophils. This could indicate a new possible application for acoustofluidics, but further testing is needed to confirm the results. With the results from the practical work done for this thesis in conjunction with the review of other studies results, the conclusion can be that automated acoustofluidic platforms such as the AcouWash has a tremendous potential within the field of cell handling compared to manual centrifugation methods where human error and potential cell viability issues are proving harder to ignore.
Keywords: Cell handling; Microfluidics; Acoustofluidics; Cell wash; Recovery; Washing efficiency; Cell viability